Sensory Processing in Williams Syndrome: Individual differences and changes over time - Powell, Bradley (J Autism Dev Disord, 2021)
This study examined individual differences as well as the development of sensory processing difficulties in children with Williams syndrome (WS) using a cross-sectional (Experiment 1) and longitudinal design (Experiment 2). In Experiment 1, a clustering approach of sensory processing scores suggested two groups. Experiment 2 showed that the clusters identified in Experiment 1 were not stable across development, especially for those with high sensory impairments at either time point. Yet, most children experienced high impairments in sensory registration at both time points, suggesting impaired registration is a core phenotype of sensory processing in children with WS across development. Possible mechanisms, limitations and implications are discussed.